Phyto- and Bacterioplankton During Early Spring Conditions in the Baltic Sea and Response to Short-Term Experimental Warming - von Scheibner, Markus; Herlemann, Daniel P. R.; Lewandowska, Aleksandra M.; Jürgens, Klaus (Frontiers in Marine Science, 2018)
Predicted increases in sea surface temperatures are expected to shift the balance between autotrophic production and the heterotrophic degradation of organic matter towards a more heterotrophic system. For early phytoplankton spring blooms at low water temperature the impact of rising temperatures has been mainly investigated in mesocosm experiments, while field observations are scarce. During a Baltic Sea research cruise we examined early spring bloom conditions, characterized by low temperatures (0 – 3°C), and performed on-board warming experiments to compare the responses of phyto- and bacterioplankton production to an increase in temperature. In the northern Baltic Sea, the low phytoplankton biomass indicated pre-bloom conditions. In the southern Baltic Sea, a diatom-dominated phytoplankton bloom with increased primary production (PP) occurred. Associated with this bloom were increases in bacterial production (BP) and bacterial abundance as well as shifts in bacterial community composition towards an increased proportion of Gammaproteobacteria and Bacteroidetes. However, the low BP/PP ratios (average: 1.2% ±0.14%) indicated weak coupling between the bacterial and phytoplankton communities. Short-term warming (6 h, Δ+6°C) significantly enhanced PP (mean Q10 1.4) and especially BP (mean Q10 2.3). Hence, the higher water temperature increased both carbon flow into the bacterial community and bacterial processing of organic matter, thereby confirming previous experimental studies. By contrast, BP/PP ratios remained relatively low after warming (average: 1.7% ± 0.5%), unlike in previous mesocosm experiments performed at comparable temperatures and with similar plankton communities. Overall, these results imply that bacterial activities are suppressed during early phytoplankton blooms at low temperatures in the Baltic Sea and are not substantially altered by short-term warming events.